2015
DOI: 10.1111/gwmr.12092
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Monitoring to Support Development of BMPs for Groundwater Protection: The Abbotsford‐Sumas Aquifer Case Study

Abstract: The Abbotsford‐Sumas Aquifer is arguably the most studied case in Canada of groundwater nitrate contamination associated with agricultural production. Underlying some of the most productive agricultural land in Canada, this highly vulnerable trans‐boundary aquifer provides a unique case study on the opportunities and challenges of addressing water quality issues. A groundwater monitoring program initiated in the early 1990s has been important in tracking spatial and temporal variation in groundwater nitrate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 49 publications
(87 reference statements)
2
63
0
Order By: Relevance
“…The risk of NO 3 contamination is also enhanced in sandy soils with limited water‐holding capacity, high water inputs as rainfall and/or irrigation (Power and Schepers, 1989; Strebel et al, 1989), and where oxic groundwater does not support denitrification (Rivett et al, 2008). Despite considerable efforts to develop improved agricultural practices (Raun and Schepers, 2008), groundwater NO 3 concentrations have exceeded the drinking water guidelines for human health for decades in some jurisdictions (Exner et al, 2014; Zebarth et al, 2015), with increasingly important implications for public water supply management.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of NO 3 contamination is also enhanced in sandy soils with limited water‐holding capacity, high water inputs as rainfall and/or irrigation (Power and Schepers, 1989; Strebel et al, 1989), and where oxic groundwater does not support denitrification (Rivett et al, 2008). Despite considerable efforts to develop improved agricultural practices (Raun and Schepers, 2008), groundwater NO 3 concentrations have exceeded the drinking water guidelines for human health for decades in some jurisdictions (Exner et al, 2014; Zebarth et al, 2015), with increasingly important implications for public water supply management.…”
mentioning
confidence: 99%
“…The quantification of groundwater NO 3 loading associated with a specific agricultural field (i.e., set of management practices) so that water quality improvements can be objectively assessed is a major challenge (O'Donnell, 2012; Zebarth et al, 2015). In many cases, soil zone techniques to measure NO 3 leaching from the root zone are commonly used on small (<0.05 ha) experimental plots where groundwater zone monitoring is not tractable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Intensive agricultural cropping (i.e., raspberry, blueberry [ Vaccinium corymbosum L.]) and poultry production are important land uses over this aquifer. Associated land application of synthetic fertilizers and manure has resulted in a history of elevated groundwater nitrate (Zebarth et al, 1998; Zebarth et al, 2015). A 1993 regional study of ASA groundwater using nitrate isotopes reported that animal manure was the primary source of groundwater nitrate (Wassenaar, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…That understanding of the effects of soil pH on the nitrification process has important economic implications, given evidence that the blueberry crop commonly has greater N uptake (Poonnachit and Darnell 2004) and greater plant growth (Peterson et al 1988) when N is supplied in NH ' 4 form compared with NO ( 3 form. The effects of soil acidification on nitrification also have important environmental implications because many of the fields being converted to blueberry are located over the transboundary AbbotsfordÁSumas Aquifer, an important source of potable water that is highly susceptible to NO ( 3 contamination (Zebarth et al 2015).…”
mentioning
confidence: 99%